First report of two braconid genera Syntretus Foerster and Xynobius Foerster from India with description of one new species - Gupta, Ankita; Achterberg, Cornelis Van; Pattar, Rohit; H.m., Hemanth Kumar (Zootaxa, 2023)
Two genera, namely Syntretus Foerster (Braconidae: Euphorinae) and Xynobius Foerster (Braconidae: Opiinae), are reported for the first time from India. One new species, Syntretus curvatus Gupta, van Achterberg & Pattar, sp. nov. is described and illustrated from southern India. Xynobius chrysops Wu, van Achterberg, Sheng & Chen, 2018, described from Vietnam, is reported newly from India.